Development of liquid sequencing valves by controlling air-flow to perform biomedical processes on centrifugal microfluidic platforms / Wisam Salah Hussein Al Faqheri - Wisam Salah Hussein, Al Faqheri (2015)

(untitled)
This thesis presents three different liquid valving methods for the centrifugal microfluidic platform, namely vacuum/compression wax valve, passive liquid valve (PLV), and check valve. The mechanism of the proposed valves is simply based on sequencing the liquid flow by controlling air-flow inside the microfluidic network. Specifically, the wax valve and passive liquid valve utilize a volume of trapped air in the source chamber or the destination chamber to control the burst frequency of the liquid. In contrast, the check valve controls the direction of the air to control the flow direction of the pumped liquid. Compared with the previously proposed valves, this mechanism prevents any direct contact between the valving materials and the sample/reagents. This will reduce the chance of sample/reagents contamination, and allow the use of wider range of valving materials. As a proof of concept, liquid metering, liquid switching, and liquid swapping are conducted using the proposed valving methods. Furthermore, Bradford assay for protein concentration detection, and enzyme linked-immunosorbent assays (ELISAs) for dengue are demonstrated to show the capability of the developed valves to perform biomedical applications. The results illustrate that the valves reduce the required spinning frequency to perform the microfluidic processes on the centrifugal platforms. In addition, the presence of physical barriers improves the ability of the developed valves to reduce vapour and contamination effect. Furthermore, the proposed valves show additional advantages such as the simplicity of fabrication and implementation, reversibility and multi-actuation, and compatibility with biomedical applications. Finally, the demonstration of the ELISA and the Bradford assays illustrate the ability of the presented valves to be integrated in any multistep biomedical and chemical application on the centrifugal microfluidic platform.